Isolation and identification of Arcobacter species from environmental and drinking water samples - Talay, Funda; Molva, Celenk; Atabay, Halil Ibrahim (Folia microbiologica, 2016)
Water plays an important role in the transmission of Arcobacter spp. to animals and humans. The aim of this study was to isolate and characterize Arcobacter spp. from 115 different water samples (66 sewage, 25 rivers, 16 spring water, and 8 drinking water) in Izmir, Turkey. In total, 41 samples (35.7 %) were found positive for Arcobacter spp. by the genus-specific PCR. Arcobacter butzleri was detected in 39 out of 115 samples (33.9 %) including 24 sewage, 13 rivers, and 2 spring water. The remaining Arcobacter spp. (n = 2) isolates could not be identified by m-PCR and 16S rRNA gene sequencing. Based on the phenotypic characterization, most of the Arcobacter species (87.8 %) indicated weak catalase activity. In addition, there were differences in phenotypic patterns among isolated species during growth at 37 °C under microaerobic and aerobic conditions, in the presence of 2 % (39/41) and 3.5 % (32/41) NaCl and 0.04 % TTC (39/41) and on MacConkey agar (38/41). The results of this study indicated that environmental water samples are common sources for Arcobacter spp. Therefore, effective control measures should be taken to protect human health.
Keywords: Arcobacter; DNA bakterií; DNA, Ribosomal; Temperature; Sequence Analysis, DNA; aerobióza; Aerobiosis; chlorid sodný; teplota; Water Microbiology; RNA ribozomální 16S; Turecko; RNA, Ribosomal, 16S; Culture Media; kultivační média; sekvenční analýza DNA; DNA, Bacterial; Turkey; ribozomální DNA; Bacterial Typing Techniques; mikrobiologie vody; Sodium Chloride; techniky typizace bakterií